PENGEMBANGAN BAHAN AJAR BERBASIS ETNOMATEMATIKA MOTIF BATIK JAMBI MENGGUNAKAN CANVA PADA MATERI SIMETRI LIPAT DAN SIMETRI PUTAR KELAS III SEKOLAH DASAR - Rahmani, Resya; Sastrawati, Eka; Zahyuni, Violita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop ethnomathematics-based teaching materials incorporating Jambi batik motifs using Canva for the topic of reflection symmetry and rotational symmetry in third-grade elementary school and to determine their validity and practicality. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of the Analyze, Design, Development, Implementation, and Evaluation stages. The research subjects were a third-grade teacher and students. Data were collected through validation questionnaires completed by material experts, media experts, and language experts, as well as response questionnaires from teachers and students to assess the practicality of the product. The validation results showed percentages of 96% from the material expert, 96% from the media expert, and 88% from the language expert, all categorized as very valid. The practicality test results indicated 96% from the teacher’s response, 90% in the small group trial, and 92.2% in the large group trial, all categorized as very practical. Based on these findings, the developed teaching materials are considered very valid and very practical, making them suitable for use as contextual teaching materials in elementary mathematics learning.